Dendrobium officinale polysaccharide promotes angiogenesis as well as follicle regeneration and hair growth through activation of the WNT signaling pathway - Yujin Zhang; Qing Tang; Bijun Zeng; Fengjiao Wang; Meijunzi Luo; Pan Huang; Ling Chen; Haizhen Wang (Regenerative Therapy)
Introduction: Hair loss is one of the common clinical conditions in modern society. Although it is not a serious disease that threatens human life, it brings great mental stress and psychological burden to patients. This study investigated the role of dendrobium officinale polysaccharide (DOP) in hair follicle regeneration and hair growth and its related mechanisms. Methods: After in vitro culture of mouse antennal hair follicles and mouse dermal papilla cells (DPCs), and mouse vascular endothelial cells (MVECs), the effects of DOP upon hair follicles and cells were evaluated using multiple methods. DOP effects were evaluated by measuring tentacle growth, HE staining, immunofluorescence, Western blot, CCK-8, ALP staining, tube formation, scratch test, and Transwell. LDH levels, WNT signaling proteins, and therapeutic mechanisms were also analyzed. Results: DOP promoted tentacle hair follicle and DPCs growth in mice and the angiogenic, migratory and invasive capacities of MVECs. Meanwhile, DOP was also capable of enhancing angiogenesis and proliferation-related protein expression. Mechanistically, DOP activated the WNT signaling and promoted the expression level of β-catenin, a pivotal protein of the pathway, and the pathway target proteins Cyclin D1, C-Myc, and LDH activity. The promotional effects of DOP on the biological functions of DPCs and MVECs could be effectively reversed by the WNT signaling pathway inhibitor IWR-1. Conclusion: DOP advances hair follicle and hair growth via the activation of the WNT signaling. This finding provides a mechanistic reference and theoretical basis for the clinical use of DOP in treating hair loss.